Understanding Sentence Roles and Argument Structures: A Syntactic Study of EFL Students - Niswatun Nafi'ah; Bochari, Siska Bochari; Usman, Sriati Usman; Hastini, Hastini (Language Circle: Journal of Language and Literature, 2025)
This study aims to identify the most difficult argument structures and argument roles in sentences identified by English as a Foreign Language (EFL) students, as well as the factors that contribute to such difficulties. The study collected data using a descriptive quantitative method, relying on quantitative descriptive data through statistical analysis. focused on 36 fifth-semester students from Class B of the English Education Study Program at Tadulako University, who were selected through purposive sampling with statistical analysis, tests, and questionnaires. The results of the research showed some key findings: (1) the most difficult argument structure for students to identify is the sentence with two arguments, which appears with a total frequency of 60; (2) the most difficult argument role for students to identify is the experiencer; and (3) five main factors affect students' ability to identify roles and arguments in sentences, namely prior knowledge, interest and motivation, learning strategies, teaching methods, and learning environment. Future researchers can discuss thematic roles that have not been addressed in this study.